Dampak Kapasitas Fiskal terhadap Penurunan Kemiskinan: Suatu Analisis Simulasi Kebijakan - Lisna, Vera; Sinaga, Bonar M.; Firdaus, Muhammad; Sutomo, Slamet (UI Scholars Hub, 2013)
This study examines the impacts of fiscal capacity on the acceleration of poverty alleviation through a dynamic simultaneous equations model using empirical data of 23 provinces and conducting historical simulation. The increasing of fiscal capacity from local taxes and tax-revenue sharing have significant impact on poverty reduction, particularly in agricultural household, which has the largest share in number of poor in Indonesia indicated by larger decline of agricultural headcount index than industrial and trade headcount index. However, the increasing of General Allocator Fund/Dana Alokasi Umum (DAU) has negative impact on agricultural headcount index. The policy implication is to increase revenue from taxation by local governments as the impact is more effective in accelerating poverty reduction.